The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s42990-020-00045-2
|View full text |Cite
|
Sign up to set email alerts
|

Integrated isotopic and organic geochemical constraints on the depositional controls and source rock quality of the Neogene Kalamaki sedimentary successions (Zakynthos Island, Ionian Sea)

Abstract: This study investigates the oxygen and carbon (δ 18 O, δ 13 C) stable isotope ratios, as well as the organic geochemical features of the 146-m-thick composite Kalamaki section located in the southwest margin of the Hellenic Fold and Thrust Belt (Zakynthos Island). The section includes Late Miocene-Pliocene pre-evaporitic, evaporitic, and post-evaporitic deposits. The obtained bulk geochemical data (Rock-Eval II, bitumen extraction, and fractionation) and biomarker compositions indicate poor-fair source-rock po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 89 publications
1
4
0
Order By: Relevance
“…Between 7.16 to 6.88 Ma and 6.80 to 6.54 Ma, mean BIT values of 0.73 indicate a more terrigenous/soil source of organic matter that contrast BIT indices of 0.46, indicating an dominantly aquatic production for the interval between 6.87 and 6.80 Ma. This observation is consistent with results from Crete (Ploutis section) and Zakynthos (Kalamaki section) indicating a mixed origin of the organic matter during the Late Miocene (Kontakiotis et al, 2020(Kontakiotis et al, , 2021. The Nile and the Saharan rivers may have served as the main east Mediterranean suppliers of clastic sediments during Tortonian-Messinian (Gladstone et al 2007), with additional contributions from mainland Greece (Karakitsios et al, 2017), western Anatolia, and the proto-Crete islands due to their proximity and position within the Aegean-Mediterranean domain.…”
Section: Alkenone Production and Organic Matter Sourcessupporting
confidence: 88%
“…Between 7.16 to 6.88 Ma and 6.80 to 6.54 Ma, mean BIT values of 0.73 indicate a more terrigenous/soil source of organic matter that contrast BIT indices of 0.46, indicating an dominantly aquatic production for the interval between 6.87 and 6.80 Ma. This observation is consistent with results from Crete (Ploutis section) and Zakynthos (Kalamaki section) indicating a mixed origin of the organic matter during the Late Miocene (Kontakiotis et al, 2020(Kontakiotis et al, , 2021. The Nile and the Saharan rivers may have served as the main east Mediterranean suppliers of clastic sediments during Tortonian-Messinian (Gladstone et al 2007), with additional contributions from mainland Greece (Karakitsios et al, 2017), western Anatolia, and the proto-Crete islands due to their proximity and position within the Aegean-Mediterranean domain.…”
Section: Alkenone Production and Organic Matter Sourcessupporting
confidence: 88%
“…The organic matter abundance is an important geochemical index to measure the quality of black organic-rich shale to generate gas [15][16][17][18]. As an important part of the organic-rich shale, organic matter abundance provides a necessary material basis for shale gas resources [19,20].…”
Section: Characteristics Of Organic Matter In the Benxi Formation Shalementioning
confidence: 99%
“…Previous studies have shown that in the Benxi Formation in the eastern Ordos Basin, a barrier coastal sedimentary system is mainly developed, and shelf sedimentary system is developed locally [14,23]. The sedimentary system can be subdivided into several microfacies, including sand flat, mixed flat, mud flat, marl flat, barrier sand bars, lagoon mud, and mud continental shelf microfacies [16]. In the Hutian Member at the bottom of the Benxi Formation, iron-aluminum-bearing mudstone and shale is mainly developed, which are the initial deposits of the Late Paleozoic epeiric sea, and superimposed on the underlying Majiagou Formation, which has experienced 150 million years of exposure and denudation after the deposition of Majiagou Formation [23].…”
Section: Sedimentary Environment Of the Benxi Formation Shalementioning
confidence: 99%
“…The OM is the prerequisite for shale gas formation and its sedimentary environment is directly related to hydrocarbon generation. The factors controlling OM enrichment can be summarized into two categories: OM input factors (e.g., paleoproductivity, paleoclimate, and terrigenous detrital input) and preservation condition factors (e.g., redox conditions, paleowater depth, and sedimentation rates) [17][18][19][20]. Three modes of OM enrichment have been proposed: (1) the high productivity model [9]; (2) the anoxic preservation model [21,22]; and (3) superposition of the two models above [23,24].…”
Section: Introductionmentioning
confidence: 99%